MOBILE LEARNING BERBASIS HTML 5 DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Irpan Nawawi (Jurnal Perspektif, 2019)
The purpose of this study was to find out the application of HTML 5-based mobile learning in improving student learning outcomes in Thaharah material PAI subjects; student responses to the application of HTML 5-based mobile learning on Thaharah material PAI subjects; and the application of HTML 5-based mobile learning that has a significant effect on learning outcomes in Thaharah material PAI subjects. The research method used is Pre-Experimental in the form of one group time series design. The study was conducted at the Biology Education Study Program of IPI Garut and the sample used was 1 grade 1 semester 1 year 2018/2019 student. This design uses only one group, namely the experimental group without the control group. Before being given treatment, the experimental group was first given prestige, then given treatment with the application of HTML 5-based mobile learning and after that was given a post. The results of this study can be concluded that the application of HTML 5-based mobile learning can improve student learning outcomes in PAH subjects Thaharah; Student responses strongly agree with the implementation of HTML 5-based mobile learning on Thaharah PAI subjects, and the application of HTML 5-based mobile learning that has a significant effect on learning outcomes in Thaharah material PAI subjects.